2015
DOI: 10.1007/s00705-015-2448-5
|View full text |Cite
|
Sign up to set email alerts
|

Association of TNF-α gene promoter region polymorphisms in bovine leukemia virus (BLV)-infected cattle with different proviral loads

Abstract: Tumor necrosis factor alpha (TNF-a) is a pleiotropic cytokine involved in the immune response against viral and other infections. Its expression levels are affected by a polymorphism in the promoter region of the gene. Bovine leukemia virus is a retrovirus that infects cattle and develops two different infection profiles in the host. One profile is characterized by a high number of proviral copies integrated into the host genome and a strong immune response against the virus, while the most relevant property o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
15
0
4

Year Published

2016
2016
2023
2023

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 15 publications
(20 citation statements)
references
References 25 publications
1
15
0
4
Order By: Relevance
“…Similar results were reported by Lendez et al (2015) in whose study cows with the G/G genotype of TNFα polymorphism at position -824 (AG) were significantly more often classified as BLV + with HPL than BLV + with a low proviral load (LPL).…”
Section: Discussionsupporting
confidence: 77%
See 2 more Smart Citations
“…Similar results were reported by Lendez et al (2015) in whose study cows with the G/G genotype of TNFα polymorphism at position -824 (AG) were significantly more often classified as BLV + with HPL than BLV + with a low proviral load (LPL).…”
Section: Discussionsupporting
confidence: 77%
“…The correlation between TNFα gene polymorphism and resistance/susceptibility to mastitis (Ranjan et al 2015), tuberculosis (Cheng et al 2016) and EBL has been investigated in a limited number of studies (Konnai et al 2006;Bojarojc-Nosowicz et al 2015;Lendez et al 2015).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, a tendency toward an increased BLV provirus load in cattle with the TNF-α -824 G/G homozygote was observed when compared to the A/A homozygote or genotype A/G. Lendez et al (2015), analysing a large population of cattle with HPVL or LPVL, revealed a significant association between LPVL and a low frequency of the G/G genotype at position -824. That means that an animal carrying this polymorphism most probably belongs to the HPVL group.…”
Section: Discussionmentioning
confidence: 88%
“…It must be considered that expression of BoLA DRB3 might be influenced by polymorphisms in other surrounding genes. An important gene of the immune system that has been linked to the BoLA region is the promoter region of tumor necrosis factor-alpha (TNF-α): both genes are located in the q22 arm of the bovine chromosome 23 and in linkage disequilibrium (LENDEZ et al, 2015). Concerning BLV infection, TNF-α is closely related with the immune response against viral dissemination, stimulating the elimination of infected lymphocytes (KABEYA et al, 1999).…”
Section: Discussionmentioning
confidence: 99%